Victim-to-Victim Intergenerational Cycles of Child Maltreatment: A Systematic Scoping Review of Theoretical Frameworks - Marshall, Carley; Langevin, Rachel; Cabecinha-Alati, Sarah (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents)

(untitled) (Canada Research Chair in Interpersonal Traumas and Resilience/Chaire de recherche du Canada sur les traumas interpersonnels et la résilience, 2022)
Objectives: Child maltreatment is a serious problem worldwide associated with numerous developmental and psychological problems that can impede children’s short and long-term functioning. The negative effects of maltreatment may put children on a trajectory where they are likely to experience later abuse and even abuse their own children. While studies have focused primarily on the intergenerational transmission of maltreatment (victim-to-perpetrator cycles), there are studies, albeit fewer, documenting cycles of intergenerational continuity of maltreatment (victim-to-victim cycles; e.g., child sexual abuse). Clear theoretical frameworks are lacking from studies on intergenerational maltreatment. This review aimed to systematically identify theories, theoretical or conceptual frameworks that have been used to explain the victim-to-victim cycles of maltreatment.